DNA Typing of Mycobacterium bovis Isolates from Badgers (Meles meles) Culled from Areas in Ireland with Different Levels of Tuberculosis Prevalence - Claire Furphy; Eamon Costello; Denise Murphy; Leigh A. L. Corner; Eamonn Gormley (Veterinary Medicine International)
Badgers (Meles meles) have been implicated in the transmission of Mycobacterium bovis infection to cattle in Ireland and UK. Recent studies in Ireland have shown that although the disease is endemic in badgers, the prevalence of disease is not uniform throughout the country and can vary among subpopulations. The extent to which the prevalence levels in badgers impact on the prevalence in cattle is not known. Previously, DNA fingerprinting has shown that M. bovis strain types are shared between badgers and cattle, and that there are a large number of strain types circulating in the two species. In this study we have carried out spoligotyping and variable number tandem repeat (VNTR) analysis of M. bovis isolates from two groups of badgers, representing a wide geographic area, with different tuberculosis prevalence levels. The results of the typing show that there is no geographic clustering of strain types associated with prevalence. However, two VNTR profiles were identified that appear to be associated with high- and low-prevalence M. bovis infection levels, respectively. In addition, spoligotyping and VNTR analysis has provided evidence, for the first time, of multiple infections of individual badgers with different M. bovis strains.